Ecotoxicological effects of jute retting on the survival of two freshwater fish and two invertebrates - Mondal, Debjit Kumar (Ecotoxicology (London, England), 2008)
Severe deterioration of water quality occurs during jute retting in ponds, canals, floodplain lakes, and other inland water bodies in the rural areas of West Bengal in India. Attempts were made to evaluate changes in the physicochemical parameters of water caused by jute retting, and their impact on the survival of two species of freshwater fish (Labeo rohita and Hypophthalmicthys molitrix) and two species of freshwater invertebrate (Daphnia magna, a Cladocera, and Branchiura sowerbyi, an Oligochaeta). Results showed that jute retting in a pond for 30 days resulted in a sharp increase in the BOD (>1,000 times) and COD (>25 times) of the water, along with a sharp decrease in dissolved oxygen (DO). Free CO(2), total ammonia, and nitrate nitrogen also increased (three to five times) in water as a result of jute retting. Ninety-six-hour static bioassays performed in the laboratory with different dilutions of jute-retting water (JRW) revealed that D. magna and B. sowerbyi were not susceptible to even the raw JRW whereas fingerlings of both species of fish were highly susceptible, L. rohita being more sensitive (96 h LC(50) 37.55% JRW) than H. molitrix (96 h LC(50) 57.54% JRW). Mortality of fish was significantly correlated with the percentage of JRW